Validation of Selected Ethno-veterinary Practices through Farmer Participatory Research Approach in Jalpaiguri District of West Bengal - Chandra, Sourav; Chakrabarty, A.; Biswas, S.; Guha, C.; Sarkar, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted in high altitude, densely tribal populated, forest fringe areas of sub-Himalayan Terai agro-climatic zone of Jalpaiguri district of North Bengal. The study was confined in the Maynaguri and Metiali block of Jalpaiguri district, mainly focusing on the villages. A sample of 65 resource persons was fixed for collection and documentation of ethno-veterinary practices or Indigenous Technical Knowledge (ITK) in livestock and wildlife in forest fringe areas of the district. At the end of the survey in total 105 ethno-veterinary practices used in livestock and wildlife were collected for proper documentation. Out of 105 documented ITKs, 10 ranked ethno-veterinary practices with five replications in each case were brought under validation through clinical trial using both ethno-veterinary and allopathic medicine by the 10 experimenter resource person following Farmer Participatory Research (FPR) approach. From the 10 best selected ITKs three were taken into consideration. Data collected from the respondents on several criteria were subjected to one way analysis of variance. To test the difference of mean amongst alternatives, multiple range test, i.e. Honest Significant Difference (HSD) Tukey’s test was used. The study revealed that ethno-veterinary medicine comprised of indigenous ingredients was favourably accepted by the mahouts and farmers to treat Sajan in elephant, external non-specific wound in cattle and yolk-gall in cattle owing to its household availability of ingredients, least side-effect, easy availability and less cost involvement made the present medicament viable option. Through, trial this may be concluded as considering many fold beneficial criteria, ethno-veterinary practice using indigenous technique was better alternative as farmers’ choice in the study area.